Implementasi Prinsip-Prinsip Demokrasi dalam Sistem Hukum Tata Negara Indonesia - Triadi, Irwan; Sulaeman, Akhfa Kamilla; Zevanya, Cristella; Audra, Rasyanda; Rangoraja, Amudi Panigori; Harahap, Aura Nasya Madhani (LANCAH: Jurnal Inovasi dan Tren, 2024)
This research presents a review of the implementation of democratic principles in the Indonesian constitutional legal system. By discussing the implementation of democratic principles in the Indonesian constitutional law system. In the context of constitutional law, democratic principles such as popular sovereignty, equal rights, free and secret elections, as well as accountability and transparency are important foundations in running the government. The research method used is normative juridical, while the type of research is library research, the activities are carried out by collecting data related to the title which is literature. Analysis of the implementation of democratic principles in the Indonesian constitutional law system shows that there are still many challenges faced, such as corruption, weak public participation, and the fulfillment of human rights. To improve the implementation of democratic principles, this research recommends efforts such as strengthening transparency, accountability, public participation, and the protection of human rights. Thus, this research hopes to contribute to the development of a more effective and sustainable democratic system in Indonesia.